Planejamento do processo de produção mais limpa em uma empresa metal-mecânica - Tagliari, Leandro Dóro (2012)
The present research addresses environmental issues in a metal-working company and how this can make your manufacturing process appropriate to the methodology of cleaner production, which is the continuous application of an integrated preventive environmental strategy to processes, products and services, to reduce the risks that are relevant to humans and the environment. It is a methodology to be applied in companies, seeking solutions to environmental impacts, generating economic benefits at all stages of production activities. The cleaner production, applied in the company in study, aims to identify the stages of the manufacturing process, characterizing the main aspects and environmental impacts arising from the production of tipper buckets in order, to obtain an environmental diagnosis for the company. The cleaner production, applied in the enterprise, aims to identify the stages of the manufacturing process, characterizing the main aspects and environmental impacts arising from the production of tipper buckets in order to obtain an environmental assessment for the company. For the implementation of this process make sure required several concepts, such as cleaner production, manufacture of tipper bucket, economic analysis and layout. The results obtained in the research identified that the company under study is not adequate to the methodology of cleaner production and activity proposals have been drawn up for the solid waste problems, such as: steel residue, cloth and sandpaper residue, effluents, waste liquids such as paints and solvents, atmospheric effluents, as the metallic smoke; through economic analysis it was possible to demonstrate to business owners future earnings to the owners of minimization and reduction of manufacturing costs, as well as the environmental benefits, evidencing the company a future environmental and culture in everyday life, the adoption of more rational conduct, aiming at integrated management thinking on the planet and the beings that live here.